Simple, rapid, and efficient purification of M13 phages: The Faj-elek method - Gizem Kılıç; Esma Aybakan; Neda Tatlıoğlu; Gökçen Özgün; Tanıl Kocagöz; Erkan Mozioğlu (PLoS ONE, 2025)
M13 bacteriophages (phages) are used as very important tools in molecular biology, biotechnology and, nanotechnology. Many methods have been developed so far for the purification of these phages. However, it is important that phages retain their infecting properties, especially in biotechnological applications such as phage display technology. The most widely used is the PEG precipitation method, but it has some limitations such as impurities and reduced infectivity. To overcome them, we developed a new method for purification of M13 bacteriophages using syringe filters made of cellulose acetate membranes with a pore diameter of 0.22 µm. Phages were aggregated so that they could remain on the filters and for this purpose, the pH of the phage cultures was reduced to 3. The phage cultures were filtered and then the phages were recovered in tris-buffered saline (TBS) buffer (pH 10.5) by reversing the filter. The recovery rate was 250% higher than the standard PEG method. This new Faj-elek method offers an alternative to existing methods, allowing cheaper, easier and faster purification of M13 phages using syringe filters available in every research laboratory.